Epistemic Cognition in the Formation of Students' Memories and Narrative Competence - Purnomo, Arif; Kurniawan, Ganda Febri; Romadi, Romadi; Karimi, Amir; Fadhila, Qonita (Universitas Negeri Semarang, 2024)
This research explores the influence of epistemic cognition and memory on students' understanding and narrative competence in learning the history of the Independence Revolution at SMA N 1 Semarang (a High School), using a qualitative case study approach. Data was obtained from classroom observations, student, and teacher interviews, as well as analysis of documents related to curriculum and learning practices. The research results show that understanding epistemological concepts, such as the nature of historical knowledge, influences students' understanding of historical material. Students who better understand the nature of historical knowledge tend to relate the material to personal and social experiences and construct critical historical narratives. The role of memory in shaping students' narrative competence is also important; consistency in remembering the chronology and relationship of events as well as the influence of emotions influence students' understanding. Student involvement, such as participation in discussions and teacher support, also influences the quality of learning. In conclusion, understanding epistemic cognition and the role of memory can help design effective learning strategies, while research implications highlight the importance of responsive curriculum development, support for teacher professional development, and collaboration between teachers.